The Influence of Social Media on Public Perception of Crime and Law Enforcement - Kartono; Yanto, Oksidelfa; Salim, Agus (International Journal of Law Social Sciences and Management, 2025)
This research examines the influence of social media on public perception of crime and law enforcement in the urban communities of Jakarta and South Tangerang. The aim is to analyse how social media shapes the narrative of crime, trust in law enforcement, and public views on legal policies. The method used is qualitative phenomenology with data collection techniques including in-depth interviews, participant observation, and digital document analysis. Data were analysed using the Miles and Huberman model. The research findings indicate that social media plays a significant role in shaping biassed perceptions, creating "collective anxiety," and triggering public pressure on law enforcement agencies based on the logic of virality. In conclusion, social media has transformed into a powerful space for information circulation as well as a tool for social control, making it necessary to optimise its use in legal communication strategies to enhance transparency and public participation.